A Closer Look at the Birth Order Effect on Early Cognitive and School Readiness Development in Diverse Contexts - Luo, Rufan; Song, Lulu; Chiu, I-Ming (Frontiers in Psychology, 2022)
Using the Early Childhood Longitudinal Study–Birth Cohort data, we examined the effect of birth order (firstborn vs. later-born) on children’s cognitive skills at 24 months and school readiness (i.e., math and literacy) skills at age 4 years. Previous research in the U.S. using predominantly English-speaking, low-risk samples suggests that firstborns tend to show better early cognitive and school readiness skills than later-born children. However, results of the current study showed that although there was a firstborn advantage in low-risk or English-speaking families, in high-risk or language minority families, later-born children showed equivalent or even better skills than firstborn children. Our moderated mediation models revealed that children’s engagement in home learning activities mediated the relation between birth order and developmental outcomes, and families’ cumulative risks and language minority status moderated the mediation pathways. These findings underscore the complex associations between birth order and early development in diverse ecological contexts.